Penerapan Model Pembelajaran Take and Give untuk Meningkatkan Keterampilan Membaca Pemahaman Siswa Kelas V - Salam, Rosdiah; Achmad, Widya Karmila Sari; Hamzah, Aslia (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2024)
This research aims to improve the reading comprehension skills of class V students at SDN No. 48 Inp. Tullu Bulan, Sendana District, Majene Regency, uses the Take and give learning model. The approach used is descriptive qualitative with the Classroom Action Research (PTK) method. The research subjects involved 10 students, consisting of 7 women and 3 men. Data was collected through observation, tests and documentation, then analyzed using qualitative data analysis techniques. The results of the research showed that there was an increase in students classical and individual reading comprehension skills from cycle I to cycle II. In cycle I, student activity was in the poor category, while in cycle II, student activity increased to the good category. So it can be concluded that the Take and give learning model can improve reading comprehension skills of class V students at SDN No. 48 Inp. Tullu Bulan, Sendana District, Majene Regency.